Jain point laparoscopic entry in contraindications of Palmers point - Jain, Nutan; Srivastava, Sakshi; Bayya, Sri Lakshmi Prasanna; Jain, Vandana (Frontiers in Surgery, 2022)
Background This study was conducted to assess the efficacy of the Jain point to overcome the contraindications of Palmer's point. The Jain point lies on the left side of the abdomen at the L4 level, 10–13 cm lateral to the umbilicus. Due to its anatomical location, the Jain point is free from adhesions because postsurgical adhesions are encountered usually in the midline or the right side. Methods This is a retrospective study conducted at a high-volume tertiary care referral center for advanced gynecological laparoscopic surgery, enrolling 8,586 patients who underwent laparoscopy at the center from January 2011 to March 2022. In this paper, we analyze 2,519 patients with a history of previous surgeries, who were operated using the Jain point. Results In the 2,519 patients with a history of previous surgeries, the Jain point port was found to be adhesion free, regardless of the location of the scars, the number and type of previous surgeries, and those in whom Palmer's point was contraindicated. No major complications were reported, except for one case (0.04%) of small bowel injury, which was managed intraoperatively. The Jain point continued to function as the main ergonomic working port. Conclusion The Jain point offers an alternate safe entry port in previous surgery cases for laparoscopic surgeons of various specialties, like general surgeons, urologists, oncologists, and bariatric surgeons, to overcome the contraindications of Palmer's point. The Jain point also acts as the main ergonomic working port, whereas Palmer's point becomes redundant after initial entry.